Educational Supervision: An Analysis of Models, Approaches, And Techniques of Educational Supervision in Higher Education - Nur Rochbani, Ita Tryas; Nurdianingsih, Fitri (Zabags International Journal of Education, 2023)
This research aims to conduct research by applying descriptive analysis techniques using library research. Testing the validity of the data was carried out by triangulating the data from references, both in terms of method and in terms of sources. The results of this research indicate that the implementation of educational supervision should not only be carried out by lecturers but also apply to the entire academic community, including education staff. The involvement of all components of the academic community through various models, approaches and techniques of educational supervision by lecturers, rectors, education staff, foundations, students, the community and government are very necessary for the progress of a higher education institution.